2017
DOI: 10.17161/fec.v38i2.6816
|View full text |Cite
|
Sign up to set email alerts
|

The Call for Collaboration in Teacher Education

Abstract: Neither general nor special education alone has either the capacity or the vision to challenge and change the deep-rooted assumptions that separate and track children and youths according to presumptions about ability, achievement, and eventual social contribution. Meaningful change will require nothing less than a joint effort to reinvent schools to be more accommodating to all dimensions of human diversity. (Ferguson, 1995, p. 285) As the number of students who are struggling in schools grows, the need fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 21 publications
1
6
0
6
Order By: Relevance
“…Participants further revealed that in-service training of regular teachers in teaching and learning strategies of children with ASD would facilitate the inclusion of these children in mainstream classrooms. This finding aligns with previous studies which have found that teachers need professional development in order to be informed and knowledgeable about ASD and about individualisation strategies for children with ASD in mainstream classrooms (Allday et al 2013;Humphrey and Parkinson 2006;Lynch and Irvine 2009;Sheffield 2008;Winn and Blanton 2005). Similarly, Humphrey (2008), Lindsay and McPherson (2012), and Maich and Belcher (2012) found that grounding teacher in-service training in the unique needs of children with ASD facilitates inclusion of these children in mainstream classrooms.…”
Section: Discussionsupporting
confidence: 88%
“…Participants further revealed that in-service training of regular teachers in teaching and learning strategies of children with ASD would facilitate the inclusion of these children in mainstream classrooms. This finding aligns with previous studies which have found that teachers need professional development in order to be informed and knowledgeable about ASD and about individualisation strategies for children with ASD in mainstream classrooms (Allday et al 2013;Humphrey and Parkinson 2006;Lynch and Irvine 2009;Sheffield 2008;Winn and Blanton 2005). Similarly, Humphrey (2008), Lindsay and McPherson (2012), and Maich and Belcher (2012) found that grounding teacher in-service training in the unique needs of children with ASD facilitates inclusion of these children in mainstream classrooms.…”
Section: Discussionsupporting
confidence: 88%
“…This finding resonates with the 'core expertise' of inclusive pedagogy which demands teachers' attention to individual differences between children while actively avoiding the marginalization of some children and/or the exclusion of particular children including children with additional needs (Kim & Rouse, 2011;Pantic & Florian, 2015). Similarly, previous studies revealed that inclusion provides quality education for all while respecting diversity and the diverse needs and abilities, characteristics and learning expectations of the children and communities, eliminating all forms of discrimination (Forlin, 2010;Naicker, 2007;Winn & Blanton, 2005). Regardless of participants' overall exhibition of understanding of inclusion, they were not articulate regarding the relativity of its meaning and the conceptual complications that abound in defining it which indicated their inadequate professional grounding in the philosophy.…”
Section: Discussionmentioning
confidence: 99%
“…Mainstream teachers require several basic skills for successful inclusion including a basic knowledge of the characteristics of children with disabilities (Agbenyega, 2007;Berry, 2010;Florian, 2009) and a comprehension of their role and responsibility in the special education process (Ncube, 2006;Winn & Blanton, 2005). Pre-school teachers are integral in serving children at risk of disabilities and affording inclusive practices to children with disabilities (Idol, 2006;Odom et al, 2011;Rafferty & Griffin, 2005).…”
Section: Basic Mainstream Teacher Skills Needed For Successful Inclusionmentioning
confidence: 99%
“…The concept of collaboration is observed to be an interactive approach, in which multiple cooperators gather to work on a voluntary basis and take decisions for a purpose. In addition, in order collaboration to be ensured and sustained, stakeholders should take common responsibilities to work and make decisions on the equal, voluntary and participative basis (Cook, & Friend, 1991, p. 6;Cook, & Friend, 2010;Friend, & Cook, 1992), and possess the skills of interaction with multiple people, effective problem solving and taking responsibilities (Thousand et al 2006;Winn & Blanton, 2005). It was seen that the results obtained from the study and the results of the studies in the literature on collaboration had similar structures.…”
Section: Extended Abstractmentioning
confidence: 99%